PERSPECTIVE OF THE COMMUNITY ON TECHNOLOGY-BASED TRANSPARENCY IN FINANCIAL REPORT OF THE TORAJA CHURCH SION ANUTAPURA CONGREGATION, PALU CITY - Timang, Katresya Jezyca; Zahra, Femilia (Penelitian dan Pengembangan Ilmu, 2025)
The purpose of this research is to understand the congregation's opinion on technological transparency in the presentation of financial reports at the Toraja Church Sion Anutapura Congregation in the city of Palu. The descriptive qualitative method with triangulation techniques—interviews, observations, and documentation—was used. The research results show that one important aspect in building trust between the congregation and the church management is honesty. The use of technology is considered to increase congregation participation and facilitate access to financial reports in PDF format via WhatsApp. By conveying information in a structured and open manner, the congregation becomes more engaged in church life. The church has addressed the issue of digital literacy, especially among elderly congregants, by providing reports in both print and digital formats. This research also shows that technology-based transparency can enhance accountability and strengthen the relationship between the management and the congregation. Therefore, the financial information system used in church governance should be expanded with this technology.